The degree to which secondary school teachers in Tabuk city practice procedural research in the light of professional development standards - Al-Marzouq, Ahmed Mohammed; Najmi, Ali Hussein (Journal of Educational and Psychological Sciences, 2022)
This study aimed to trace the degree to which secondary school teachers in Tabuk city practice procedural research and to determine the significance of the statistical differences between the average responses of the study sample members to the degree of the practice of the study sample members of the procedural research that are attributed to the following variables (sex – academic qualification – a type of qualification – specialization – years of service). The researcher used the descriptive-analytical method because of its relevance to the nature and objectives of the study. Therefore, a questionnaire was designed to measure the degree to which secondary school teachers in Tabuk city practice procedural research in the light of professional development standards. It was distributed electronically to a stratified random sample of (373) male and female teachers, representing the study population, which consists of all secondary school teachers in the Tabuk educational region, and their number is (1697) male and female teachers, including (745) male and (952) female teachers. The study has shown several results, including the general degree of Tabuk secondary school teachers’ practice of procedural research was high, with a mean of (3.63). The results have revealed a statistically significant difference at the significance level (0.05) in the degree to which teachers practice procedural research according to the gender variable and in favor of females. Considering the results, the researcher recommends a number of recommendations, including: Training secondary school teachers on how to perceive problems and determine their scope, and to use primary and secondary sources in collecting information about the problem in question.